Assessment of Sleep Disorder among Autistic Children - Ali D. Abbas (Kufa Journal for Nursing Sciences)
Objectives: The study objectives are to identify sleep disorders among children with autism and to identify the association between sleep disorders for children with autism and their demographic characteristics including (age, gender, housing, educational level for mother, occupation status of the mother, and monthly income).